Murine cytotoxic activated macrophages inhibit aconitase in tumor cells. Inhibition involves the iron-sulfur prosthetic group and is reversible. - Drapier, J C (1986)
Previous studies show that cytotoxic activated macrophages cause inhibition of DNA synthesis, inhibition of mitochondrial respiration, and loss of intracellular iron from tumor cells. Here we examine aconitase, a citric acid cycle enzyme with a catalytically active iron-sulfur cluster, to determine if iron-sulfur clusters are targets for activated macrophage-induced iron removal. Results show that aconitase activity declines dramatically in target cells after 4 h of co-cultivation with activated macrophages. Aconitase inhibition occurs simultaneously with arrest of DNA synthesis, another early activated macrophage-induced metabolic change in target cells. Dithionite partially prevents activated macrophage induced aconitase inhibition. Furthermore, incubation of injured target cells in medium supplemented with ferrous ion plus a reducing agent causes near-complete reconstitution of aconitase activity. The results show that removal of a labile iron atom from the [4Fe-4S] cluster, by a cytotoxic activated macrophage-mediated mechanism, is causally related to aconitase inhibition.